Cu/Bi metal-organic framework-based systems for an enhanced electrochemical transformation of CO2 to alcohols. (October 2019) - Albo, Jonathan; Perfecto-Irigaray, Maite; Beobide, Garikoitz; Irabien, Angel
Graphical abstract: Highlights: Cu(II) and Bi(III)-based MOFs are synthesized and used for CO2 electroconversion. The MOF-based GDEs give mainly alcohols (methanol and ethanol) and formic acid. Reaction selectivity can be controlled by Cu/Bi loading and current density applied. The synergy of Cu/Bi in CO2 conversion is related with enhanced binding energies. The materials remain pseudo-stable after five hours of operation. Abstract: This work assesses the performance of Cu(II) and Bi(III)-based metal-organic framework (HKUST-1 and CAU-17, respectively) blends into the electroreduction of CO2 to alcohols in a filter-press electrochemical cell. The bimetallic materials are supported onto porous carbon paper to form gas diffusion electrodes with a favorable continuous electrochemical conversion of CO2 to methanol and ethanol, together with formic acid and gas-phase products (i.e. hydrogen, carbon monoxide and ethylene) in a 0.5 M KHCO3 aqueous solution. The maximum reaction rates and faradaic efficiencies for CO2 conversion to methanol and ethanol are rCH3OH =29.7 μmol·m −2 ·s -1 ( FE  = 8.6%) and rC2H5OH =48.8 μmol·m −2 ·s -1 ( FE  = 28.3%), respectively, at j  = 20 mA·cm −2 which enhanced the values obtained at homometallic Cu and Bi-based materials independently. This denotes a synergic effect of Cu and Bi-based MOFs, associated with a favored interplay between the actives sites and reaction intermediates, prompting methanol formation and CC coupling reaction to ethanol. The results also show that reaction selectivity to produce alcohols can be controlled by Cu/Bi loading in the electrode surface and current density applied to the system. A 12% bismuth content seems to be the optimum for the production of alcohols ( FEalcohols  = 36.9%, Salcohols  = 0.32). Regarding the current density, CO2 reduction is more selective to methanol with a j =10 mA·cm −2 ( FECH3OH  = 18.2%), while at j  = 20 mA·cm −2, ethanol becomes the dominant CO2 reduction alcohol ( FEC2H5OH  = 28.3%). The performance of the Cu/Bi-MOFs remains also pseudo-stable after 5 h of operation denoting the potential of the mixed metal-organic systems for the utilization of CO2 .